Peter's death in Rome? Back to front and upside down - Bockmuehl, Markus (Scottish journal of theology, 2007)
Contrary to periodic challenges from a viewpoint of historical scepticism or relativism, Jerome's late fourth-century description of Simon Peter may be said to represent a critical and consensual account of the Apostle's demise in Rome as this was reflected in early Christian memory of the first two centuries, both in the East and in the West. Three centuries earlier, the much-debated passage in 1 Clement 5 represents (for all its ambiguities) an integral strand of such living memory – citing the founding apostles' death for their faith according to local Roman tradition while discreetly airbrushing the specific circumstances of their demise. It is significant, finally, that local memory of Peter's martyrdom remained confined to Rome and was never subject to competing claims elsewhere.